Particulate Anion Sorbents as Electrolyte Additives for Lithium Batteries. (23rd September 2020) - Shen, Li; Wu, Hao Bin; Liu, Fang; Shen, Jianqiang; Mo, Runwei; Chen, Gen; Tan, Guoqiang; Chen, Juner; Kong, Xueqian; Lu, Xing; Peng, Yiting; Zhu, Jian; et al.
Abstract: The performance of lithium batteries is heavily governed by the transport of ions within the electrolytes. Commercial liquid electrolytes, however, generally exhibit a low lithium‐ion transference number, causing concentration polarization, side reactions, and deteriorated battery performance. Herein, a novel class of electrolyte additives based on particles of metal–organic framework is proposed to immobilize the anions while allowing efficient transport of lithium ions in the electrolytes. The use of such additives effectively increases the lithium‐ion transference number, enhances the rate capability, and prolongs the cycling life, which provides a facile yet effective strategy toward lithium batteries with dramatically improved performances. Abstract : This work reports a particulate additive strategy for improving the transport efficiency of lithium ions in electrolyte of lithium batteries, which is achieved by adsorbing and immobilizing anions in metal–organic frameworks. Such particulate anion sorbents effectively increase the lithium‐ion transference number of electrolyte and prolong the battery durability at high current density.